Predictive factors for regression of gastric MALT lymphoma after anti-Helicobacter pyloritreatment. Issue 3 (1st March 2001) - Ruskoné-Fourmestraux, A; Lavergne, A; Aegerter, P H; Megraud, F; Palazzo, L; de Mascarel, A; Molina, T; Rambaud, J-C L; ,
Abstract : BACKGROUND AND AIMS: Discrepant remission rates (41–100%) have been reported for patients with localised low grade gastric mucosa associated lymphoid tissue (MALT) lymphoma after eradication of Helicobacter pylori . The aim of this study was to explain these discrepancies and to determine the predictive factors of gastric lymphoma regression after anti- H pylori treatment. PATIENTS AND METHODS: Forty six consecutive patients with localised gastric MALT lymphoma (Ann Arbor stages IE and IIE ) were prospectively enrolled. All had gastric endoscopic ultrasonography and H pylori status assessment (histology, culture, polymerase chain reaction, and serology). After anti- H pylori treatment, patients were re-examined every four months. RESULTS: Histological regression of the lymphoma was complete in 19/44 patients (43%) (two lost to follow up). Median follow up time for these 19 responders was 35 months (range 10–47). No regression was noted in the 10 H pylori negative patients. Among the 34 H pylori positive patients, the H pylori eradication rate was 100%; complete regression rate of the lymphoma increased from 56% (19/34) to 79% (19/24) when there was no nodal involvement at endoscopic ultrasonography. There was a significant difference between the response of the lymphoma restricted to the mucosa and other more deep seated lesions (p<0.006). However, using multivariate analysis, the only predictive factor of regression was the absence of nodal involvement (p<0.0001). CONCLUSION: In H pylori positive patients with localised gastric MALT lymphoma, carefully evaluated and treated without any lymph node involvement assessed by endoscopic ultrasonography, complete remission of lymphoma was reached in 79% of cases.